2018
DOI: 10.1093/comjnl/bxy005
|View full text |Cite
|
Sign up to set email alerts
|

Cache Freshness in Named Data Networking for the Internet of Things

Abstract: The Information-Centric Networking (ICN) paradigm is shaping the foreseen future Internet architecture by focusing on the data itself rather than its hosting location. It is a shift from a host-centric communication model to a contentcentric model supporting among others unique and location-independent content names, in-network caching and name-based routing. By leveraging the easy data access, and reducing both the retrieval delay and the load on the data producer, the ICN can be a viable framework to support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Some proposals were devised in IoT sensor networks, with the main target of reducing the data retrieval latency and limit the energy consumption [4][5][6]. Other works considered caching transient contents in wired networks segments [7,8].…”
Section: Cache Inconsistency In Existing Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some proposals were devised in IoT sensor networks, with the main target of reducing the data retrieval latency and limit the energy consumption [4][5][6]. Other works considered caching transient contents in wired networks segments [7,8].…”
Section: Cache Inconsistency In Existing Solutionsmentioning
confidence: 99%
“…Such an effect is particularly exacerbated in VANETs, due to the broadcast nature of the wireless medium that facilitates sharing of data, also of useless data, if they expired. However, literature on caching transient contents in NDN is almost unexplored in VANETs and still in its early stage for Internet of Things (IoT) contents [4][5][6] and wired networks [7,8]. To fill this gap, the following contributions are provided in this paper:…”
Section: Introductionmentioning
confidence: 99%
“…The analysis results revealed that, the topology of the network and the routing algorithms used to generate forwarding information might have a significant impact on the performance of a given caching strategy. In [111], it was pointed out that IoT data is transient and frequently updated by the producer. Therefore, IoT data imposes strict requirements in terms of information freshness.…”
Section: A In-network Cachingmentioning
confidence: 99%
“…IoT content objects are transient in nature and frequently updated [184]. In addition, storage capacity of IoT devices is limited, and IoT applications also have specific data freshness requirements.…”
Section: Energy-aware Caching Resource Managementmentioning
confidence: 99%